Reassembling of albumin-bound paclitaxel mitigates myelosuppression and improves its antitumoral efficacy via neutrophil-mediated targeting drug delivery - Yuxin Chen; Lulu Han; Xiaoyan Qiu; Meng Wang; Zheng Chen; Ying Cai; Yong Xin; Yanfang Lv; Ankang Hu; Dafei Chai; Liantao Li; Huizhong Li; et al. (Taylor & Francis Group, 2022)
Albumin-bound paclitaxel (abPTX) has been widely used in cancer treatment. However, dose-related side effects, such as myelosuppression, restrict its clinical application. Cell-based targeting drug delivery is a promising way to mitigate systematic side-effects and improve antitumoral efficacy. In this study, we demonstrated that reassembled abPTX could be engulfed by neutrophils in vivo and delivered to tumor site, thus improving therapeutic efficacy and mitigating myelosuppression. First, in vitro analysis confirmed that reassembling of abPTX formed uniform and stable serum albumin nanoparticles (NP-abPTX) with size of 107.5 ± 2.29 nm and reserved the ability to kill tumor cells. Second, we found that NP-abPTX could be engulfed by activated neutrophil in vitro and in vivo but do not affect neutrophils' function, such as chemotaxis and activation. In a murine tumor model, we further proved that local radiotherapy (RT) induced inflammation activated peripheral neutrophils to capture venous infused NP-abPTX and carry them into tumor tissue. As compared to abPTX, infusion of NP-abPTX dramatically enhanced inhibition of tumor growth treated by local RT and mitigated hematotoxicity. Therefore, our study demonstrated a novel strategy to mitigate side-effects and to improve tumor killing efficacy of abPTX through neutrophil-mediated targeting drug delivery.